A woman's life [videorecording (DVD)] - Brizé, Stéphane, 1966-; Chemla, Judith; Darroussin, Jean-Pierre; Moreau, Yolande, 1953-; Maupassant, Guy de, 1850-1893 (Kino Lorber, 2017)
A fragmented account of the life of Jeanne as she sets out on the path of adult life and gradually experiences the harsh realities of a woman's life in the nineteenth century.